2022
DOI: 10.3390/machines10090734
|View full text |Cite
|
Sign up to set email alerts
|

Auto-Encoder-Enabled Anomaly Detection in Acceleration Data: Use Case Study in Container Handling Operations

Abstract: The sudden increase in containerization volumes around the globe has increased the overall number of cargo losses, infrastructure damage, and human errors. Most critical losses occur during handling procedures performed by port cranes while sliding the containers to the inner bays of the ship along the vertical cell guides, damaging the main metal frames and causing the structure to deform and lose its integrity and stability. Strong physical impacts may occur at any given moment, thus in-time information is c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…AutoEncoder is one of the techniques utilized in deep neural networks for identifying anomalies in robotic sensor signals [31]. This approach involves training on previously observed states from the experience replay buffer (RB) [32], and then predicting future states based on those observations.…”
Section: Autoencoder Architecturementioning
confidence: 99%
“…AutoEncoder is one of the techniques utilized in deep neural networks for identifying anomalies in robotic sensor signals [31]. This approach involves training on previously observed states from the experience replay buffer (RB) [32], and then predicting future states based on those observations.…”
Section: Autoencoder Architecturementioning
confidence: 99%
“…To verify the superiority of the intelligent fault diagnosis method proposed in this paper, some classical class imbalanced diagnosis frameworks are selected as the comparison frameworks, such as those based on SMOTE [19], ADASYN [46], VAE [47] and GAN [48]. The specific comparison results on two class imbalance data sets with different levels of severity are shown in Figure 21.…”
Section: Comparison With Other Diagnosis Frameworkmentioning
confidence: 99%
“…Further investigations resulted in the development of the impacts detection methodology (IDM), which has proved its value in handling operations as an embedded solution in the Klaipeda city port [23]. It was experimentally tested and the prototype system was validated in actual handling activities at LKAB "Klaipedos Smelte" container terminal [24]. As our previous research suggested, as well as the results of [1,[25][26][27] indicate, the topic of container structural health monitoring is a hot topic, and therefore improvements of the IDM must be researched more.…”
Section: Introductionmentioning
confidence: 99%